2023
DOI: 10.47360/1995-4484-2023-100-105
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of anti-DFS70 in immunoinflammatory rheumatic diseases (review)

Abstract: The relevance of the problem of immunoinflammatory rheumatic diseases (IIRD) for modern medicine is determined by their high prevalence in the population, the difficulty of early diagnosis, the rapid development of disability and poor life prognosis. Recent data on the significance of anti-DFS70 have opened up new possibilities for optimizing the step-by-step diagnosis of IIRD. The detection of these antibodies can help in the interpretation of a positive result for antinuclear antibodies (ANA) by indirect imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…According to the results of various studies, a negative association has been observed between isolated anti-DFS70 antibodies and SLE and other SARDs [32], in which these autoantibodies are found in isolation in less than 1% of patients (except for this figure in children with SLE, where it was 1.8%-though these data are based on the results of just one study) (Table 3) [33]. It can be stated that we observe a lower frequency of anti-DFS70 occurrence in this patient cohort compared to healthy individuals.…”
Section: Assessment Of Detecting Dfs70 Antibodies In Clinical Practicementioning
confidence: 99%
“…According to the results of various studies, a negative association has been observed between isolated anti-DFS70 antibodies and SLE and other SARDs [32], in which these autoantibodies are found in isolation in less than 1% of patients (except for this figure in children with SLE, where it was 1.8%-though these data are based on the results of just one study) (Table 3) [33]. It can be stated that we observe a lower frequency of anti-DFS70 occurrence in this patient cohort compared to healthy individuals.…”
Section: Assessment Of Detecting Dfs70 Antibodies In Clinical Practicementioning
confidence: 99%